An inherently flame-retardant polyamide 6 containing a phosphorus group prepared by transesterification polymerization. (20th October 2020) - Zhang, Shengming; Fan, Xuesong; Xu, Chaochen; Ji, Peng; Wang, Chaosheng; Wang, Huaping
Abstract: During the hydrolysis polymerization of caprolactam, melt polycondensation requires that the stoichiometry of the carboxyl-terminal and amine-terminal groups be kept in balance, which greatly limits the copolymerization modification of polyamide 6 (PA6). In this paper, we designed a PA6 prepolymer and modified 9, 10-dihydro-10-[2, 3-di(hydroxycarbonyl)propyl]-10-phosphaphenanthrene-10-oxide (DDP) monomers so that they have the same ethylene glycol ester end groups. Based on the principle of transesterification to achieve chain growth, an intrinsic flame-retardant polyamide 6 (FR-PA6) is prepared. Our research results show that the FR-PA6 prepared by the synthetic route outlined in this article not only maintains the excellent performance of polyamide 6 but also allows the molecular weight growth of the polyamide 6 polymer to behave independently of the stoichiometric balance of the terminal groups. This method breaks the limitation of the copolymerization reaction caused by hetero end groups after the hydrolysis of caprolactam and ensures a stable degree of polymerization when a high proportion of modifier is added. When the EDE content is increased to 8%, the phosphorus content in the polymer reaches 4640 ppm, the limiting oxygen index reaches 29.5%, and the vertical combustion reaches V-0. The flame-retardant mechanism is analysed by cone calorimetry and pyrolysis gas chromatography-mass spectrometry. This method can prepare flame-retardant PA6 on traditional polyester equipment and can be widely used in the fields of plastics and fibres. Graphical abstract: Image 1 Highlights: A transesterification reaction was introduced into the copolymerization modification of PA6 for the first time. The flame-retardant PA6 retains the excellent performance of PA6 and is endowed with excellent flame retardancy. A high proportion copolymerization of modified components can be achieved. The synthetic route of FR-PA6 is suitable for traditional polyester equipment and has industrialization prospects.